2000
DOI: 10.1063/1.1308526
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence of Ge/Si self-assembled quantum dots grown by chemical vapor deposition

Abstract: We have fabricated light-emitting diodes on Si operating in the near-infrared. The active region of the p–i–n diodes consists of Ge/Si self-assembled quantum dots. The Ge islands were grown in an industrial 200 mm single-wafer chemical vapor deposition reactor. The photoluminescence and the electroluminescence of the islands are resonant in the spectral range around 1.4–1.5 μm wavelength. The electroluminescence is observed up to room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The localization of electrons in the Ge/Si interface is mainly determined by the Coulomb interaction, i.e., by the indirect exciton binding energy, which is constant and equals 25 meV [36]. The latter value is close to kT at room temperature, making an observation of the QDSL band at room temperature quite difficult [8][9][10][11][12][13]26]. In our highly strained Sb-doped QDSLs the potential well for electrons is deeper due to the tensile strain-induced lowering of the conduction band.…”
Section: (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…The localization of electrons in the Ge/Si interface is mainly determined by the Coulomb interaction, i.e., by the indirect exciton binding energy, which is constant and equals 25 meV [36]. The latter value is close to kT at room temperature, making an observation of the QDSL band at room temperature quite difficult [8][9][10][11][12][13]26]. In our highly strained Sb-doped QDSLs the potential well for electrons is deeper due to the tensile strain-induced lowering of the conduction band.…”
Section: (A)mentioning
confidence: 99%
“…Although arrays of self-assembled Ge islands grown by the StranskiKrastanow mode on silicon have been studied quite intensively, just a few research teams have reported about PL [8,9] and electroluminescence (EL) data [10][11][12][13]. Probably, due to the low emission intensity, the internal quantum efficiency (QE) measured at room temperature for Ge/Si light emitting diode (LED) at 1.42 lm has been reported only in two studies with the following results: 5 · 10 -4 % [11] and 0.015% [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Ge(Si) islands luminescent properties also has both the fundamental and applied aspects. The applied interest is associated with a signal in the wavelength range 1.3-1.7 µm being observed up to room temperatures in the luminescence spectra of structures with Ge(Si)/Si(001) islands [4,5]. Fundamental investigations of the Ge(Si) islands luminescence are aimed to reveal the features of the radiative recombination of charge carriers in nanostructures based on the indirect band semiconductors, particularly of the influence of charge carriers confinement on their recombination [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk silicon in this wavelength range is transparent, which makes it possible to use waveguides on its basis and opens new avenues for the integration of optical and electronic components on one silicon substrate. In the last few years, various teams [6][7][8][9] reported on successes in observing the electroluminescence (EL) at room temperature from structures with Ge(Si) islands. The best results in the region of formation of light-emitting diode structures with Ge(Si) islands in the wavelength range of 1.3-1.9 µ m were obtained in [10], where the EL external quantum efficiency amounted to ~0.04% at room temperature.…”
Section: Introductionmentioning
confidence: 99%